KEBUTUHAN INFORMASI PETANI GUREM (Kasus Desa Rowo Kecamatan Kondangan Kabupaten Temanggung) - Hanifah Ihsaniyati (Universitas Sebelas Maret, 2010)
Information has a very important role in our efforts to reach goals. It serves to reduce uncertainty, particularly as input to solve problems, make decisions plan and improve knowledge. The objectives of this study were to identify the peasants’ need for informations. The reach used a qualitative approach with a constructivism paradigm. It was found in the research site that to maintain all of the jobs they were serious engaged in, information had become an important factor. They need for informations was inseparable from the problems they experience in both farming and non-farming activities. They need not only farming hut also non-farming informations. The information need of among the peasants were different depending on, the type of peasant. The information need of the peasant that take height risk different from the peasant that take low risk.